A New Scale of Readiness for Health Care Students to Encounter Partner Abuse - Sawyer, Simon (Journal of interpersonal violence, 2022)
Partner abuse (PA) is associated with significant morbidity and mortality worldwide. Health care practitioners regularly encounter patients experiencing PA and require comprehensive education on how to respond. This study describes the creation and validation of a new measure of readiness to encounter patients experiencing PA for health care practitioners and students.Initial item development and content validation were informed by expert feedback. Psychometric properties were assessed using data collected from Australian health care students, using Principal Components Analysis (PCA) and Confirmatory Factor Analysis (CFA). Internal consistency, inter-scale correlations, and test?retest analysis were performed.An initial pool of 67 items was reduced to 48 following content validation by 5 experts as a measure of construct validity. A total of n = 926 responses were collected, which were randomly split into two groups to perform a PCA and CFA. The PCA resulted in a 31-item version, which was further reduced to a 27-item version following the CFA, containing four factors. Internal consistency and test?retest analyses demonstrated good reliability.The produced scale is a 27-item measure of readiness to encounter patients experiencing PA, which has demonstrated good psychometric properties with a sample of Australian health care students. Results indicate that self-efficacy and Emotional-readiness are a large component of readiness. The scale may be used to measure the readiness of a cohort, or as a pre and post-intervention measure, and results may provide insight into the educational needs of a cohort.